Trisomy 9 Mosaicism Diagnosed In Utero - Hironori Takahashi; Satoshi Hayashi; Yumiko Miura; Keiko Tsukamoto; Rika Kosaki; Yushi Itoh; Haruhiko Sago (Obstetrics and Gynecology International)
We present three cases of trisomy 9 mosaicism diagnosed by amniocentesis with ongoing pregnancies after referral to our center due to fetal abnormalities. Two cases were associated with severe fetal growth restriction (FGR), each of which resulted in an intrauterine fetal demise (IUFD) in the third trimester. The other case involved mild FGR with a congenital diaphragmatic hernia and resulted in a live birth with severe development delay. A major prenatal finding of trisomy 9 mosaicism is FGR. Fetuses with trisomy 9 mosaicism can rarely survive in the case of severe FGR.